Modelling of tilt rotor mission performance to assess environmental impact - Ruge Montilla, Jhonn Hamberth (Cranfield University, 2012)
New technologies and new rotorcraft operations are being developed in order to meet new environmental requirements such as noise reduction and less pollutant emissions. In this project a parametric study was developed over a tilt rotor model in order to assess the environmental impact in terms of operational parameter and fuel burned looking at pollutant emission released into the air such as NOx, CO, UHC, PM, CO2 & H2O In order to perform the study previously stated, a computational tool build on Simulink titled tilt rotor mission performance was developed to run a single mission profile as a base line making different operational variations on every mission segment looking at deviations over fuel burned and pollutant emissions. The contribution of pollutant emissions during the cruise segment was compared to other phases obtaining 80% of CO2 and H2O, 75% of CO and UHC, 77% of NOx, and 78% of PM. Also, comparing the distance flown of the tilt rotor with some turboprop aircraft, it was found that the fuel burned and levels of CO2 are higher using tilt rotor rather than turboprop aircraft. On the other hand this is much better than helicopters.
Keywords: Rotorcraft; Mission Level; Atmosphere; Pollutant Emissions; Model